The Effect of an Innovative Biofeedback SKOL-AS(®) Treatment on the Body Posture and Trunk Rotation in Children with Idiopathic Scoliosis—Preliminary Study - Kamelska-Sadowska, Anna M. (Medicina (Kaunas), 2019)
Background and Objectives: The deformity in idiopathic scoliosis (IS) is three dimensional and effective correction involves all three planes. Recently, the biofeedback method has been implemented in the treatment of scoliosis. The aim of this study was to evaluate the effectiveness of an innovative biofeedback SKOL-AS(®) postural training among children with scoliosis. Materials and Methods: The target population for this study was 28 patients (25 girls and 3 boys) aged between 5 and 16 years old diagnosed and treated with progressing low-grade scoliosis. The postural diagnosis consisted of anthropometric measurements, posterior–anterior X-ray imaging, SpinalMeter(®) postural assessment and the angle of trunk rotation (ATR) assessment. The SKOL-AS(®) treatment comprised of 24 sessions conducted in lying and sitting positions, two times a week. Results: It has been shown that the postural training resulted in the decrease in the ATR value (pre- vs. post-exercise in younger: 5.55 vs. 3.0 and older patients: 5.2 vs. 3.0). The increase in height of the subjects seemed to confirm a positive effect of SKOL-AS(®) elongation treatment. In the posterior view, a statistically significant decrease in shoulder asymmetry in the sitting position in younger children has been observed. In the anterior view, the changes in the head position (based on mouth and eye symmetry) have been observed. The statistically significant increase in acromion–heel, acromion–iliac crest and posterior superior iliac spine (PSIS)–heel length values has been shown in younger children on the left side of the body. After treatment, older subjects had higher acromion–iliac crest and PSIS–heel values on the left side of the body. On the right side only PSIS–heel length was higher. In a sitting position, only a small increase in acromion–iliac crest length value has been observed. Conclusions: The SKOL-AS(®) biofeedback method could teach good postural habits and teach patients the auto-correction of the spine.